2008
DOI: 10.17221/2778-pse
|View full text |Cite
|
Sign up to set email alerts
|

Mobilisation of arsenic in soils and in rice (Oryza sativa L.) plants affected by organic matter and zinc application in irrigation water contaminated with arsenic

Abstract: The experiments were conducted to study the effects of arsenic-contaminated irrigation water, zinc and organic matter on the mobilization of arsenic in an Aeric Endoaquept in relation to rice (cv. IET 4786). The results show that the amount of extractable arsenic increased with the progress of submergence decreased with zinc application. The magnitude of such decrease varied with the Zn amount, being greater (0.70 to 1.08 mg/kg) in the treatment where zinc was applied at the rate of 20 mg/kg. With regards to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 18 publications
(20 reference statements)
5
9
0
Order By: Relevance
“…The As accumulation by the plant parts generally followed the order: root>stem>leaf>economic produce (Table 2), in agreement with the findings of Das et al,(2008). The As accumulation by the plant parts was observed to increase with the increase of added As.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The As accumulation by the plant parts generally followed the order: root>stem>leaf>economic produce (Table 2), in agreement with the findings of Das et al,(2008). The As accumulation by the plant parts was observed to increase with the increase of added As.…”
Section: Resultssupporting
confidence: 86%
“…The As contaminated groundwater had been in use in these areas for drinking as well as irrigation purpose to crops which eventually finds its way to animal and human continuum. The use of As-contaminated irrigation water in West Bengal has been found to cause accumulation of As in rice plants (Das et al, 2008). Estimates showed that As in rice and other food sources could contribute to about 30% of the total As ingestion (Huq et al, 2007).…”
mentioning
confidence: 99%
“…The pentavalent form of As was found less toxic (Weis and Weis 1991). Although As human and zoo toxicity is usually reported, many authors deal with As influence on plant growth and plant physiology (Pavlíková et al 2007, Das et al 2008). …”
mentioning
confidence: 99%
“…In contrast to this, As reduced K, Ca, Mg, Si, Fe, Zn, Cu, Rb, and Sr concentration of the sunflower plants. Interaction between As, Fe, and Zn was previously reported by Hartley and Lepp (2008) and Das, Sur, and Das (2008). They suggested that the As contamination in soils may be reduced by applying Fe oxides and Zn sulfates to the soil.…”
Section: Discussionmentioning
confidence: 70%